Pengaruh Kompetensi Guru terhadap Hasil Belajar Siswa Tingkat Sekolah Menengah Atas - Zidni Akholik Almaghfiroh; Nur Fais Zalillah; Nadia Wulidar Rohmah; Bonafid Ikrom; Alif Akbar Maulana; Didit Darmawan (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
This literature study examines the influence of teacher competence on student learning outcomes at various levels of Senior High Schools (SMA) in Indonesia. To improve student learning outcomes, teachers must be able to develop their competence in every learning process. The teacher competence in question includes pedagogical, professional, social, and personality competence. This study applies the literature review method through analysis of various relevant scientific sources. The results of the study revealed that teacher competence influences the improvement of student learning outcomes, although in some cases there are other variables such as student learning motivation and learning facilities that also contribute. Therefore, improving teacher competence needs to be a concern in efforts to improve the quality of education.